Leveraging the Decision Support System and Simple Additive Weighting Method for Optimal Retail Location Identification - Muhammad Ade Kurnia Harahap; Hardisal Hardisal; Ahyuna Ahyuna; Robbi Rahim (PT Mattawang Mediatama Solution, 2022)
The decision-making process is a crucial part of any business or organization, and the Decision Support System (DSS) using the Simple Additive Weighting (SAW) method is a widely used tool for evaluating multiple options or alternatives. This study aimed to determine the best location for a new retail store using the DSS and SAW method. Four criteria were considered in the evaluation process: population density, proximity to competitors, average income, and rent cost. Data was collected and analyzed, and the weighted scores were calculated using the SAW method. The results of this study showed that Location A had the highest weighted score, and thus was determined to be the best option for the new retail store. This study provides a reliable method for evaluating multiple options and determining the best one. It also highlights the advantages of using the DSS and SAW method, such as the objective decision-making process based on data and criteria, and the high reliability of the results. Additionally, this study also points out the limitations of not using the DSS and SAW method, such as the subjective decision-making process based on personal bias and low reliability of the results. The DSS SAW method can be applied in various decision-making scenarios, and this study can serve as a guide for future research and decision-making processes.